Teaching Style and Mental Representation of Teachers in Biology Learning Using Convention Picture - Ramadhan, F; Rahmat, A; Nuraeni, E (Universitas Sebelas Maret, 2018)
Activities of teacher’s working memory in representing a picture are important in the teaching and learning process. This study aimed to reveal the tendency of teacher’s mental representation and teacher’s teaching styles in biology class using convention pictures. This research used descriptive method. The research was conducted by involving four high school biology volunteer teachers of grade XI from four schools in Lebak, Banten, Indonesia. Teacher’s teaching styles were measured by questionnaires and rubrics adapted from Grasha and teacher’s mental representations were measured using worksheets and rubrics developed based on the Causal Network Elicitation Technique (CNET) model. The data obtained were analyzed qualitatively. The results showed two dominant teacher teaching styles; there were expert style and facilitator style. The mental representation of teachers when reading convention picture was in the category of good (2 teachers), adequate (1 teacher) and inadequate (1 teacher). A teacher with expert teaching style tends to have a good mental representation compared to a teacher with facilitator teaching style.